PERFORMA PEMIMPIN PEREMPUAN DI PARLEMEN - Anis Endang SM; Adinda Tessa Naumi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2019)
This research aims to seekthe performance of women leaders in the Regional House of Representativesof Bengkulu City in communicating politics and representing themselves as leaders in a "masculine" world that is considered cruel to women. This research used a descriptive qualitative method. Data were collected by using in-depth interview and observation to three women leaders.Based on the results, it could be concluded that the female parliamentary leaders conducting political communication feminine style leadership such as engaging and directing parliamentarians they led in carrying out their duties. However, when it’s needed, they remain firm, but not arrogant.